2006
DOI: 10.1007/s00520-005-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilising handheld computers to monitor and support patients receiving chemotherapy: results of a UK-based feasibility study

Abstract: This project suggests that a handheld-computer-based symptom management tool is feasible and acceptable to both patients and health professionals in complementing the care of patients receiving chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 45 publications
(78 reference statements)
4
111
0
4
Order By: Relevance
“…The system reported here is a mobile phone based, remote monitoring, advanced symptom management system (ASyMS © ) which has been developed over a period of 5 years to remotely monitor and manage chemotherapy related toxicity in patients with cancer 22,27 .…”
Section: Contributory Factors Include Poor Communication Between Patimentioning
confidence: 99%
“…The system reported here is a mobile phone based, remote monitoring, advanced symptom management system (ASyMS © ) which has been developed over a period of 5 years to remotely monitor and manage chemotherapy related toxicity in patients with cancer 22,27 .…”
Section: Contributory Factors Include Poor Communication Between Patimentioning
confidence: 99%
“…For example, Head and colleagues [35] reported that all 44 patients from the intervention arm of an RCT reported a handheld device to be very easy (85%) or easy (15%) to use. Similarly, a feasibility study reported that although 66% of 18 patients had little prior computer experience, at post-study all 11 patients who had received the intervention reported that they felt comfortable using the handheld device [36]. A similar study including a sample of 13 patients receiving palliative care reported that patients lacked confidence and experience in using technology, particularly the Internet and PDAs [40].…”
Section: Perceived Ease Of Usementioning
confidence: 98%
“…Qualitative interviews from another RCT showed that patients were positive about the real-time, fast response of the clinicianalerting facility [41]. However, interviews from a feasibility study found that some patients felt that the depth of the self-care information was insufficient and repetitive [36] and two further feasibility studies revealed variation in use of the self-care advice/information pages [39,42,46]. Yap and colleagues [49] reported that whilst over half of patients (62%) found a mobile phone, symptom-monitoring intervention useful, patients with lower education and chemotherapy-naïve patients rated the intervention significantly more useful than those with higher education (75% vs 35%) or those who had received chemotherapy before (82% vs 53%).…”
Section: Perceived Usefulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Otro ejemplo lo constituyen los denominados "juegos serios" (serious games), juegos digitales creados con propósitos que van más allá del entretenimiento, que facilitan la entrega de información médica y de herramientas de apoyo para la toma decisiones y la implicación en conductas saludables (4)(5)(6) . En los últimos años se está también comenzando a indagar acerca de la viabilidad y los beneficios asociados a la evaluación electró-nica en este tipo de pacientes, fundamentalmente mediante ordenador (7)(8)(9) , y se han generado aplicaciones móviles dirigidas a monitorizar y ayudar al manejo de la sintomatología desde casa (10)(11) , además de servir de apoyo a programas online, gracias a la posibilidad que ofrecen para registrar síntomas, recibir mensajes y acceder a módulos del programa (12) . Si bien estos desarrollos son todavía escasos, se están not only to diminish discomfort but also to promote emotional well-being, especially during medical procedures and hospitalization Key words: Virtual reality, cancer, distress, emotional well-being.…”
Section: Introductionunclassified